2001
DOI: 10.1084/jem.193.10.1169
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's Tyrosine Kinase Regulates the Activation of Gene Rearrangements at the λ Light Chain Locus in Precursor B Cells in the Mouse

Abstract: Bruton's tyrosine kinase (Btk) is a nonreceptor tyrosine kinase involved in precursor B (pre-B) cell receptor signaling. Here we demonstrate that Btk-deficient mice have an ∼50% reduction in the frequency of immunoglobulin (Ig) λ light chain expression, already at the immature B cell stage in the bone marrow. Conversely, transgenic mice expressing the activated mutant BtkE41K showed increased λ usage. As the κ/λ ratio is dependent on (a) the level and kinetics of κ and λ locus activation, (b) the life span of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 49 publications
(86 reference statements)
11
71
2
Order By: Relevance
“…We previously showed that B cells from Btk-deficient mice have a ϳ50% reduction in the frequency of Ig L chain expression, already at the immature B cell stage in the bone marrow (16). This finding implicated Btk in the regulation of the activation of the locus for V(D)J recombination in pre-B cells (16).…”
Section: Ig L Chain Usage In Btk Mutant Micementioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that B cells from Btk-deficient mice have a ϳ50% reduction in the frequency of Ig L chain expression, already at the immature B cell stage in the bone marrow (16). This finding implicated Btk in the regulation of the activation of the locus for V(D)J recombination in pre-B cells (16).…”
Section: Ig L Chain Usage In Btk Mutant Micementioning
confidence: 99%
“…IL-7-driven BM cultures and determination of IL-7-dependent proliferative responses of total BM cells have been described previously (14,16). Mature B cell fractions were purified from spleen, using standard NH 4 Cl lysis to deplete erythrocytes, followed by complement-mediated T cell lysis, as described previously (25).…”
Section: In Vitro (Pre-)b Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice lacking Btk [10][11][12], BLNK [13][14][15][16], or PLCc2 [17,18] have a milder phenotype with the predominant defect at the T2 to mature transition in the periphery. Btk -/-mice have a reduced frequency of Igk-expressing cells due to a role for Btk in Igk rearrangement in pre-B cells [19]. Several other early events in B cell development are partially impaired in mice lacking individual signalosome components.…”
Section: Introductionmentioning
confidence: 99%